Ultra filtration using gas sparging technique for treatment of natural rubber effluent - Yusoff, Harunsyah; Sulaiman, Nik Meriam; Kheireddine Aroua, Mohd (Malaysian Journal of Science, 2004)
Physical and chemical properties of natural rubber effluent have been identified to contain large amounts of non-rubber compounds and chemicals which can seriously damage or kill the natural llora and fauna of the waters when the effluent is discharged untreated. This paper presents the application of membrane technology for the treatment of natural rubber processing effluent that involves gas injection technique. During the experiments, permeate was collected and analysed for several characteristics such as total solids (TS), chemical oxygen demand (COD), biochemical oxygen demand (BOD), total nitrogen and ammoniacal nitrogen (NH3-N). The results show that the use of gas sparging technique was able to increase total permeate flux 8.3% and 145.3% compared to non-gas sparged technique condition. In terms of permeate quality, reductions achieved for total solid (TS), chemical oxygen demand (COD), biochemical oxygen demand (BOD), total nitrogen: and ammoniacal nitrogen (NHvN) were 95%, 67%, 77%, 51%, 74% respectively. For non-gas sparged technique conditions, permeate fluxes declined sharply with time due to accumulation of foulant on the membrane surface. 1 Iowevcr both conditions showed increase of total permeate flux with transmembrane pressure and feed flowrate.